INDENTIFIKASI MAKRO ALGA DI KAMPUNG ISENEBUAI DISTRIK RUMBERPON KABUPATEN TELUK WONDAMA - mogea, rina anita (VOGELKOP: Jurnal Biologi, 2023)
Algae macro is a part of sea plants and  it belongs to lower division plant.  Morphologically, there is no difference between its root, stem, dan leaf.  This plant is known as thallus.  This organism can do photosynthesis, it has clorofil and a simple reproduction  structure.  Ecologically, algae macro is involved in producing oxygen for its habitat and other sea biota.The purpose of this research is to provide information about the presence of varieties of algae macro in the Isenebuai village’s sea shore in the district of Rumberpon and  to look at the ecology, which includes the density, frequency, diversity and uniformity of algae macro.  The method used is the transect line using exploration survey technique.  The result of this research found 30 algae species.  According to the species diversity Shannon-Wiener index, the number is 1,786 or medium whereas species uniformity index, the number is 0,859 approaches 1, so that the uniformity in species is varied.